Impact of Lactobacillus plantarum ST-III on the composition of infant gut microbiota and its potential synergism with breast milk and infant formula as revealed by an in vitro study. (October 2018) - Yan, Minghui; Chen, Wanyi; Li, Nan; Ren, Jing; Chen, Chen; You, Chunping; Liu, Zhenmin
Abstract: Several studies have demonstrated the effect of probiotics on prevention of diseases in infants. However, the mechanisms remain not fully addressed. In the present study a modified standard ileal efflux medium (SIEM) was exploited in an in vitro analysis and the effect of Lactobacillus plantarum ST-III on the composition of infant gut microbiota was examined in I-chip analysis followed by qPCR confirmation. Also, the effect of ST-III, when administered in combination with breast milk and infant formula, was investigated. The results showed that ST-III could reduce the overall amount of Enterobacteria and Bacteroidetes bacteria, yet increase the abundance of Lactobacillus and certain Bifidobacterium species. Notably, some species/genus of bacteria of medical significance, e.g., Alcaligenaceae sutterella and Desulfovibrio bacteria were inhibited by ST-III. Moreover, co-administration of breast milk or infant formula could increase the abundance of ST-III, suggesting a synergistic effect between ST-III and infant formula and breast milk.